2021
DOI: 10.1177/09636625211020474
|View full text |Cite
|
Sign up to set email alerts
|

Analytical categories to describe deficit attributions in deep disagreements between citizens and experts

Abstract: Disagreements often arise from citizen–expert collaboration, as both agents share a different epistemic worldview. Fogelin, following Wittgenstein, proposed that some disagreements (i.e. deep disagreements) cannot be rationally solved when participants share different forms of life. Citizen–expert is an exemplar of this sort of disagreement. Moreover, deep disagreements are often followed by deficit attributions from one of the agents to the other, regarding their epistemic understanding, credibility, and moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The pandemic has reinforced this thinking [3]. Paradoxically, despite ongoing efforts at public engagement, public discourse has been affected by a subtle, top-down dynamic of scientism [4] that has generated scepticism [5] and sometimes even rejection of science [6], This is also known as the backfire effect [7], and it is suggested that we need to be more imaginative in presenting alternative models of scientific governance and fostering a culture of experimentation [8].…”
Section: Rethinking Scientific Governance: Beyond Deficit Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has reinforced this thinking [3]. Paradoxically, despite ongoing efforts at public engagement, public discourse has been affected by a subtle, top-down dynamic of scientism [4] that has generated scepticism [5] and sometimes even rejection of science [6], This is also known as the backfire effect [7], and it is suggested that we need to be more imaginative in presenting alternative models of scientific governance and fostering a culture of experimentation [8].…”
Section: Rethinking Scientific Governance: Beyond Deficit Thinkingmentioning
confidence: 99%
“…synoptic transfer would not deny the shortcomings of laypeople, but it would limit these shortcomings to the scientific image and equally point out the limitations of scientific experts in interpreting science in the manifest image, a stance that prohibits contributions that rely on persuasion and assume a paternalistic relationship between science and the public [4]. This would avoid the cardinal error of deficit thinking, which focuses on getting the facts right rather than understanding the interplay of information, social structures, media ecologies and socio-psychological dynamics [3].…”
Section: Applying the Framework To The Public Spherementioning
confidence: 99%